Risk factors for overcorrection of severe hyponatremia: a post hoc analysis of the SALSA trial - Huijin Yang; Songuk Yoon; Eun Jung Kim; Jang Won Seo; Ja-Ryong Koo; Yun Kyu Oh; You Hwan Jo; Sejoong Kim; Seon Ha Baek (Kidney Research and Clinical Practice, 2022)
Background Hyponatremia overcorrection can result in irreversible neurologic impairment such as osmotic demyelination syndrome. Few prospective studies have identified patients undergoing hypertonic saline treatment with a high risk of hyponatremia overcorrection. Methods We conducted a post hoc analysis of a multicenter, prospective randomized controlled study, the SALSA trial, in 178 patients aged above 18 years with symptomatic hyponatremia (mean age, 73.1 years; mean serum sodium level, 118.2 mEq/L). Overcorrection was defined as an increase in serum sodium levels by >12 or 18 mEq/L within 24 or 48 hours, respectively. Results Among the 178 patients, 37 experienced hyponatremia overcorrection (20.8%), which was independently associated with initial serum sodium level (≤110, 110–115, 115–120, and 120–125 mEq/L with 7, 4, 2, and 0 points, respectively), chronic alcoholism (7 points), severe symptoms of hyponatremia (3 points), and initial potassium level (<3.0 mEq/L, 3 points). The NASK (hypoNatremia, Alcoholism, Severe symptoms, and hypoKalemia) score was derived from four risk factors for hyponatremia overcorrection and was significantly associated with overcorrection (odds ratio, 1.41; 95% confidence interval, 1.24–1.61; p < 0.01) with good discrimination (area under the receiver-operating characteristic [AUROC] curve, 0.76; 95% CI, 0.66–0.85; p < 0.01). The AUROC curve of the NASK score was statistically better compared with those of each risk factor. Conclusion In treating patients with symptomatic hyponatremia, individuals with high hyponatremia overcorrection risks were predictable using a novel risk score summarizing baseline information.